(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Femto-second laser pulses have been used to investigate Laser-induced-periodic-surface-structures (LIPSS) formation. Scientists made great efforts to understand the involved mechanism, but the phenomenon is not yet fully understood. In this work, we used the previous techniques which lead us to control the optical properties of Copper surface and create random Nano-roughness (NR). We focused first a linearly polarized ruby laser on a surface of the Copper material, where we obtained parallel ripples, and then we looked for the macroscopic visual effects related to the type of surface Nano-structure. We used Fourier space to confirm the periodic Nano-structures on the metal surface. Which in real space presumes a semi-anisotropic distribution of periodicities and explains why the iridescence can occurs in a range of angles, if the grating is rotated along an axis perpendicular to its surface. As a result: Nano-structure formation seems possible on the surface of the Copper material. إن تشكيل بنية سطحية دوريةَ ليزرياً (LIPSS) باستخدم اليزرات النبضية (ليزر الفمتو-ثانية ) على سطوح المعادن هو أحد الاتجاهات العلمية الطروحة بقوة بسبب تطبيقاتها العلمية والهندسية الممكنة. قام العلماء في هذا الإطار بجهد كبير لفهم تلك الآلية المعقّدة التي لا تزال غير مفهومة بشكل تام. استخدمنا في هذا العمل التقنية السابقة على سطح معدن النحاس لتأكيد إمكانية تشكيل أثلام دوريةَ و جزيئات نانويّة على سطح معدن النحاس عند مسحها ضوئياً باستخدام الليزر. ركزنّا عملنا على تأثير الاستقطاب الخطي لليزر في سطح النحاس. ثم درسنا تأثير خواص الجزيئات النانوية المتشكلة في البنية الجهرية للمعدن. كنتيجة لهذا العمل يمكن التأكيد أن تشكّل الجزيئات النانويّة على سطح معدن النحاس يبدو ممكناَ ويؤثر تأثيراً مباشر في الخواص الضوئية الجهرية للمعدن.